1982
DOI: 10.1152/ajpheart.1982.242.6.h980
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial function and metabolism during acute coronary artery occlusion

Abstract: Regional changes in myocardial function and oxidative metabolism during acute coronary artery occlusion were recorded spectrophotometrically by incorporating fiber optics in the isolated rat heart perfused by Langendorff's procedure. Oxygen saturation of myoglobin, reduction of cytochrome aa3, and the dynamic wall thickness of the left ventricle were continuously and concurrently measured from absorbancy increments at 581-592 nm, 605-630 nm, and 568-592 nm, respectively. In contrast to a gradual decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In isolated rat hearts, Kanaide et al (21,22) demonstrated that the typical early dyskinesis of the ischemic region occurred when the oxygen supply appeared still sufficient for the normal mitochondrial oxidative function and when the ATP and creatine phosphate content remained at aerobic levels. In contrast, the amplitude of systolic wall thickening decreased much more gradually and without systolic bulging when anoxic perfusion, or global ischemia, was performed (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In isolated rat hearts, Kanaide et al (21,22) demonstrated that the typical early dyskinesis of the ischemic region occurred when the oxygen supply appeared still sufficient for the normal mitochondrial oxidative function and when the ATP and creatine phosphate content remained at aerobic levels. In contrast, the amplitude of systolic wall thickening decreased much more gradually and without systolic bulging when anoxic perfusion, or global ischemia, was performed (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the amplitude of systolic wall thickening decreased much more gradually and without systolic bulging when anoxic perfusion, or global ischemia, was performed (21,22). They concluded that, during acute coronary occlusion, the early dyskinesis was the result of passive extension or thinning of the ischemic wall induced by the contraction of the remaining normoperfused myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…in the rabbit heart (35), after cardioplegia (37), and with global ischemia without cardioplegia in the rat (36), while other authors could not confirm such a close relationship (16,52). Kanaide and coworkers reported that dysfunction of the ischemic region precedes a substantial loss of ATP production and content (26). Neely and coworkers (33) did not believe in a direct ATP-function relationship, they only supposed ATP to be a good indicator of tissue injury.…”
Section: ~mentioning
confidence: 99%
“…We developed front-surface NADH-fluorometry, of the whole heart, using optic fibres, the objective being to minimize optical artifacts which can arise from contractile movements (Kanaide et al, 1982). Using the Ca2+-indicator dye fura-2 and front-surface fluorometry, we measured simultaneously [Ca2 ] and force during contractions of porcine coronary arteries induced by endothelin (Kodama et al, 1989) or by okadaic acid .…”
Section: Introductionmentioning
confidence: 99%